Amalgamation of Estimation Techniques in Assessing Software Metrics and their Utilization in Project Management - Chaudhary, Swati; Singh, Madan (International Journal of Engineering and Technology, 2018)
The main reason for software-intensive acquisition programs is the poor size estimation that is not more effective. The estimation of the significant software metrics,utilization of the metrics,recording the metrics are the challenges in software estimation. The software estimation becomes a tedious task due to these challenges, which needs to be rectified. In literature, a number of techniques were proposed to resolve these challenges by the researcher. In our paper, we present a survey on the existing software estimation techniques based on the existing issues.Â Â
Keywords: Amalgamation; Software metrics; Project Management; Software effort estimation.